Coconut - Taffin, G. de. (Technical Centre for Agricultural and Rural Cooperation, 1998)
The author covers the main types of coconut palm, their origin, distribution and characteristics. Production factors such as climate, soils, breeding and plantation management are discussed, as are pest and disease control, processing and marketing.